WANITA TUNA SUSILA DI SUMATERA BARAT DAN PEMBINAANNYA (STUDI KASUS PANTI ANDAM DEWI SOLOK) - Doni Doni Nofra; Inggria Kharisma (Universitas Islam Negeri Sjech M. Djamil Djambek Bukittinggi, 2019)
Tuna Susila (WTS) women are women who sell themselves and perform sexual acts as a livelihood, in terms of religion and health, the actions of Tuna Susila (WTS) women violate the norms in living life. In overcoming their efforts, there needs to be a guidance for Women Tuna Susila (WTS) to change their mindset so that they leave acts that are not following the prevailing norms in life. They can find better jobs and develop the knowledge that is in themselves as well as the knowledge that has been given while in the institution and return to the right path. The theory used in this study is the social theory of phenomenology (phenomenology Sociology), which was put forward by Alfred Schutz, who states that human action becomes a social relationship if humans give meaning or meaning to their activities as something meaningful. This study uses qualitative methods with descriptive types to develop the problems to be studied. From the results of the study, it was concluded that the coaching process that was obtained by Women Tuna Susil (WTS) while in the Andam Dewi Solok orphanage, had made most of the Tuna Susil Women (WTS) leave their jobs as Tuna Susil (WTS) and could continue their lives towards better. Forms of guidance given to Women with Tuna Susil (WTS) at Andam Dewi Solok orphanage can be grouped into four of them: (a). Physical guidance aims to improve the physical and health conditions of Tuna Susila Women (WTS) to be able to absorb the guidance material delivered. (b). Thoughtful guidance, the aim is to guide and improve the mental or psychological of the client. (c). Community social guidance aims to lead to harmony and community life togetherness. (d). Skills guidance, the purpose of this skill is for those who are trained to gain knowledge and skills so they can open their own business from the skills they have.